A Simple Model of Housing Rental and Ownership with Policy Simulations - Andrew Coleman; Grant M. Scobie (New Zealand Government, The Treasury, 2009)
The housing market is both large and complex. This paper develops a simple model that captures the essential features of the supply and demand for housing, and which is used to evaluate the impact of a range of policy interventions. Increases in the stock of housing would reduce rents and house prices. A reduction in tax concessions for landlords would raise rents and moderate house prices. Additional subsidies for owner-occupancy would tend to reduce rents and raise house prices. Significant reductions in rents and house prices would follow a fall in the cost of housing, through, for example lower regulatory and consent costs. Falling real interest rates result in lower rents, higher house prices and lower owner-occupancy rates. Despite the widespread attention owner-occupancy rates have attracted, the paper concludes that they are not a particularly helpful guide to the state of the housing market. Typically they are quite insensitive to policy interventions, a result that follows from the integrated view of both the rental and ownership market, adopted in this study.
Keywords: R21; R31; R38; 330; Housing markets; New Zealand; rental and owner-occupancy; elasticities; rents; house prices; policy simulations; Wohneigentum; Nachfrage; Angebot; Miete; Immobilienpreis; Preiselastizität; Wohnungspolitik; Neuseeland